Integrating Local Wisdom into Child-Friendly Education: A Gender-Responsive Approach to Achieving SDG 4 and SDG 5 in Indonesian Context - Nurul Fauziah; Nadlifah Nadlifah; Agnes Fransiska Dewi; Yeni Wulandari (Journal of Contemporary Gender and Child Studies, 2025)
Previous research indicates that globalization threatens the preservation of local wisdom in early childhood education, yet studies examining the integration of local wisdom through gender-responsive child-friendly approaches remain limited. This study aims to analyze forms of local wisdom revitalization through child-friendly education at Kindergarten Level. A qualitative method was employed using in-depth interviews and participatory observation of learning activities based on local values. The findings identified three main revitalization strategies: traditional clothing usage during cultural commemorations, market days for introducing traditional foods, and habituation of local language in daily communication. Activities were designed following child-friendly education principles that respect students' potential, interests, and comfort without gender bias. Results demonstrate that this approach effectively fosters love for local culture while strengthening inclusive character formation from early age. The research implications offer an innovative model for integrating local wisdom into early childhood curriculum that is responsive to children's developmental needs and gender equality, contributing to SDG 4 and SDG 5 achievement through sustainable culture-based education.